Pembuatan Sistem Penjualan Aset 3D Blender berbasis Web menggunakan Metode Waterfall - Mahesa Dzikri Kurniawan; Bagus Hardika; Daffarizqy Prastowiyono; Muhammad Adzka; Aditya Wicaksono; Muhammad Nasir (JASIEK (Jurnal Aplikasi Sains, Informasi, Elektronika dan Komputer), 2025)
This research developed "3Dify," a web-based 3D Blender asset sales system, employing the Waterfall methodology. Its primary goal is to efficiently facilitate 3D asset acquisition, purchasing, and downloading for creators and users across diverse fields, including education and the creative industry. The development process encompassed needs analysis, UML-based design, implementation using Laravel and MySQL, and functional Black Box testing based on use cases. Implementation results confirm all features operate as expected, from administrator product management to user transactions and downloads. The system significantly enhances the efficiency of 3D asset search and distribution, demonstrating strong potential for future evolution into a digital asset e-commerce platform. Achieving a 90.91% success rate from 44 testing scenarios, this study validates the Waterfall approach's effectiveness in constructing a reliable and structured 3D asset sales system.